應用實證於肝性腦病變患者蛋白質飲食攝取的臨床決策 - 楊惠卿(Hui-Ching Yang); 林淑媛(Shu-Yuan Lin) (護理雜誌, 2013)
Patients with liver cirrhosis often develop hepatic encephalopathy complications. Reducing a patient's intake of dietary proteins as a preventive strategy is controversial and lacks of evidence support in clinical trials. This article systematically reviewed the findings of 8 clinical trials. In terms of effectiveness, liver cirrhosis patients in these studies who restricted their dietary protein intake had not improved significantly from those who consumed a normal or high protein diet. Based on this review, we developed a decision-making algorithm of protein diet regimens for hepatic encephalopathy. This article can provide a reference to nurses responsible to provide dietary instructions to patients with hepatic encephalopathy.